2022
DOI: 10.1186/s40168-021-01191-x
|View full text |Cite
|
Sign up to set email alerts
|

Host tp53 mutation induces gut dysbiosis eliciting inflammation through disturbed sialic acid metabolism

Abstract: Background Host tp53 mutations are frequently found during the early stages of colitis-associated colorectal cancer (CAC), but whether such mutations induce gut microbiota dysbiosis and chronic intestinal inflammation that contributes to the development of CAC, remains unknown. Results We found that zebrafish tp53 mutant larvae exhibited elevated intestinal inflammation, by monitoring the NFκB activity in the mid-distal intestines of zebrafish larv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 112 publications
(109 reference statements)
2
6
0
Order By: Relevance
“…We showed that FMT from the A or AN group induced mastitis in recipient mice, suggesting that gut dysbiosis is attributed to the development of mastitis [ 19 , 21 , 22 ]. Our results agree with previous findings that microbiota-liberated host SA facilitates enteric pathogen invasion and promotes host gene mutant-induced opportunistic pathogen expansion [ 34 , 65 , 66 ]. Similar findings have also been reported in other microbiota-liberated host sugars, including succinate and fucose [ 45 , 67 ], indicating that changed carbon metabolism may confer an expansion advantage for pathogens.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We showed that FMT from the A or AN group induced mastitis in recipient mice, suggesting that gut dysbiosis is attributed to the development of mastitis [ 19 , 21 , 22 ]. Our results agree with previous findings that microbiota-liberated host SA facilitates enteric pathogen invasion and promotes host gene mutant-induced opportunistic pathogen expansion [ 34 , 65 , 66 ]. Similar findings have also been reported in other microbiota-liberated host sugars, including succinate and fucose [ 45 , 67 ], indicating that changed carbon metabolism may confer an expansion advantage for pathogens.…”
Section: Discussionsupporting
confidence: 93%
“…However, the origin of microbial sialidase and how it is elevated are unclear in the present study. We confirmed that inhibition of SA release alleviated SARA-induced mastitis by zanamivir, which could be extended to previous studies showing that inhibition of sialidase is a potential strategy to improve gut dysbiosis and subsequent inflammatory responses [ 66 , 69 ]. Another potential reason for the increased SA is mucosal inflammation, in which LPS triggered host neuraminidase release through TLR4 and treatment with sialidase inhibitor attenuated inflammation caused by LPS or pathogen invasion [ 33 , 82 ].…”
Section: Discussionsupporting
confidence: 87%
“…[55] A study published in 2022 revealed that TP53 mutation mediated sialic acid metabolism imbalance and severed gut microflora dysbiosis closely related to abnormally inflammatory response. [56] Further research on the pathological mechanism of glioblastoma has shown that TP53 overexpression was accompanied by the activation of TNF-α, which led to the continuous deterioration of glioblastoma and seriously affected the quality of patient prognosis. [57] Due to extensive anti-inflammatory effects of HD, we inferred that the pharmacological mechanism of HD against IBS was significantly associated with HIF-1 signaling pathway and TNF signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 Accordingly, it is possible to directly determine causality between the gut microbiome and disease‐associated alterations in functional and mechanistic studies. 12 Studies on gut microbiome using the zebrafish model have been considered a pioneering and vital field of research in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Last but not least, germ‐free (GF) zebrafish provide a robust system for dissecting or manipulating microbial signals owing to its cost‐effectiveness and the convenience of the techniques for constructing sterile zebrafish 10,11 . Accordingly, it is possible to directly determine causality between the gut microbiome and disease‐associated alterations in functional and mechanistic studies 12 . Studies on gut microbiome using the zebrafish model have been considered a pioneering and vital field of research in recent years.…”
Section: Introductionmentioning
confidence: 99%